PENGEMBANGAN APLIKASI OPERASIONAL RESTORAN DENGAN FRAMEWORK SCRUM (STUDI KASUS: RESTORAN PT.XYZ) - Ngurah Suryantara, I Gusti; Michael, Michael; Andry, Johanes Fernandes; Ginting, Jusia Amanda (ISTEK WIDURI, 2023)
In software development, it is necessary to plan carefully, so that the software developed is in accordance with user needs. Software development without good planning will result in a patchwork of software development. To avoid the patchwork of software development, a software development framework is required. The research